Long working hours and overweight and obesity in working adults. Issue 1 (December 2016) - Kim, Byung-Mi; Lee, Bo-Eun; Park, Hye-Sook; Kim, Young-Ju; Suh, Young-Ju; Kim, Jeong-youn; Shin, Ji-Young; Ha, Eun-Hee
Abstract Background Previous studies have identified a link between gender and the various risk factors associated with obesity. We examined obesity risk factors in working adults to identify the effects of differences in body mass index (BMI) and percentage body fat (PBF) between women and men. Methods A total of 1, 120 adults agreed to participate in the study. Data from 711 participants, including 411 women and 300 men, were analyzed. Multiple logistic regression analysis was used to estimate the effects of risk factors on obesity and being overweight. In addition, the least-squares (LS) means of both BMI and PBF were estimated by analysis of covariance (ANCOVA) in a generalized linear model.  Results Increases in BMI and PBF were significantly related to an age > 50 years and long working hours in women after compensating for confounding factors. Using the PBF criterion, the odds ratio (OR) of being overweight or obese in women > 50 years of age who worked for > 9 h a day was 3.9 (95% confidence interval [CI], 1.05–11.00). For BMI, women who were > 50 years of age and worked for > 9 h a day were 3.82 times (95% CI, 1.31–11.14) more likely to be overweight or obese than those who were < 50 years of age and worked for < 9 h a day. Conclusion Obesity in working adults was associated with > 50 years of age and long working hours in women. Further studies are needed to investigate the underlying mechanisms of this relationship and its potential implications for the prevention and management of excess weight and obesity.